PEMODELAN MATEMATIKA TERHADAP KECANDUAN GAME ONLINE BERDASARKAN MODEL SEIRS PADA BERBAGAI KELOMPOK USIA DI INDONESIA - Siregar, Annisa Fadhillah Putri; Firmansyah, Firmansyah; Panjaitan, Dedy Juliandri (Majalah Ilmiah METHODA, 2024)
The mathematical model can be used to analyze many real-life problems. One of them is the case of online game addiction, which is currently rampant in Indonesia. This research will analyze the SEIRS mathematical model in the case of online game addiction experienced by various age groups. The purpose of this research is to understand mathematical modeling based on the SEIRS model for cases of online game addiction in various age groups in Indonesia. The result of this research is the mathematical model, which is , S(0) = 17; E(0) = 25; , I(0) = 6; and , R(0) = 2.